Remote sensing of the ionosphere from very low earth orbit - Timothy A. Cook; Supriya Chakrabarti (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Sequence stratigraphy and relative sea level variations in Kaštela Bay, Dalmatian coast, Croatia, and implications for the submerged palaeolandscapes and archaeology of the late Pleistocene, marine isotope stage 3 and marine isotope stage 2 - Simon Fitch; Slavica Bosnjak; Jessica W. Cook Hale; Vedran Barbarić; Timothy A. Shaw; Tanghua Li (Quaternary Science Reviews, 2025)

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

Predicting the yield of Pinus taeda (L.) using UAV LiDAR data in random forest and support vector machine models - Gunjan Barua; David R. Carter; Valerie A. Thomas; P. Corey Green; Phil Radtke; Thomas J. Pingel; Rachel L. Cook; Timothy J. Albaugh; Rafael Rubilar; Otavio Campoe; Matthew Sumnall (Forest Ecology and Management, 2025)

Quantifying above- and belowground biomass improved our understanding of site differences and demonstrated the importance of management decisions in sequestering carbon in Pinus taeda - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marshall A. Laviner; Timothy J. Shively; Vitor Aguiar; Kyle R. Peer; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Forest Ecology and Management, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Evaluating individual tree metrics calculated from unmanned aerial vehicle laser scanning as input to a conventional growth and yield model - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2025)

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Nature vs. nurture: Drivers of site productivity in loblolly pine (Pinus taeda L.) forests in the southeastern US - Vicent A. Ribas-Costa; Aitor Gastón; Sean A. Bloszies; Jesse D. Henderson; Andrew Trlica; David R. Carter; Rafael Rubilar; Timothy J. Albaugh; Rachel L. Cook (Forest Ecology and Management, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Evaluating the transferability of airborne laser scanning derived stem size prediction models for Pinus taeda L. stem size estimation to two different locations and acquisition specifications - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Erik Platt; Trevor Host; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2024)

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

Development and Validation of an Abbreviated Child and Adult Food Security Scale for Use in Clinical and Research Settings in the United States - Ana Poblacion; Stephanie Ettinger de Cuba; Deborah A. Frank; Georgiana Esteves; Lindsey J. Rateau; Timothy C. Heeren; Sharon Coleman; Maureen M. Black; Diana B. Cutts; Félice Lê-Scherban; Eduardo R. Ochoa; Megan Sandel; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

Estimation of individual stem volume and diameter from segmented UAV laser scanning datasets in Pinus taeda L. plantations - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Local adaptation and spatiotemporal patterns of genetic diversity revealed by repeated sampling of Caenorhabditis elegans across the Hawaiian Islands - Timothy A. Crombie; Paul Battlay; Robyn E. Tanny; Kathryn S. Evans; Claire M. Buchanan; Daniel E. Cook; Clayton M. Dilks; Loraina A. Stinson; Stefan Zdraljevic; Gaotian Zhang; Nicole M. Roberto; Daehan Lee; et al. (Molecular Ecology, 2022)
The nematode Caenorhabditis elegans is among the most widely studied organisms, but relatively little is known about its natural ecology. Genetic diversity is low across much of the globe but high in the Hawaiian Islands and across the Pacific Rim. To characterize the niche and genetic diversity of C. elegans on the Hawaiian Islands and to explore how genetic diversity might be influenced by local adaptation, we repeatedly sampled nematodes over a three‐year period, measured various environmental parameters at each sampling site, and whole‐genome sequenced the C. elegans isolates that we identified. We found that the typical Hawaiian C. elegans niche comprises moderately moist native forests at high elevations (500–1,500 m) where ambient air temperatures are cool (15–20°C). Compared to other Caenorhabditis species found on the Hawaiian Islands ( e.g ., Caenorhabditis briggsae and Caenorhabditis tropicalis ), we found that C. elegans were enriched in native habitats. We measured levels of genetic diversity and differentiation among Hawaiian C. elegans and found evidence of seven genetically distinct groups distributed across the islands. Then, we scanned these genomes for signatures of local adaptation and identified 18 distinct regions that overlap with hyper‐divergent regions, which may be maintained by balancing selection and are enriched for genes related to environmental sensing, xenobiotic detoxification, and pathogen resistance. These results provide strong evidence of local adaptation among Hawaiian C. elegans and contribute to our understanding of the forces that shape genetic diversity on the most remote volcanic archipelago in the world.

Effect of varied unmanned aerial vehicle laser scanning pulse density on accurately quantifying forest structure - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2022)

Financial Returns for Biomass on Short-Rotation Loblolly Pine Plantations in the Southeastern United States - Andrew Trlica; Rachel L Cook; Timothy J Albaugh; Rajan Parajuli; David R Carter; Rafael A Rubilar (Forest Science, 2021)
Rising demand for renewable energy has created a potential market for biomass from short-rotation pine plantations in the southeastern United States. Site preparation, competition control, fertilization, and enhanced seedling genotypes offer the landowner several variables for managing productivity, but their combined effects on financial returns are unclear. This study estimated returns from a hypothetical 10-year biomass harvest in loblolly pine plantation using field studies in the Coastal Plain of North Carolina and the Virginia Piedmont testing combinations of tree genotype, planting density, and silviculture. Although enhanced varietal genotypes could yield more biomass, open-pollinated seedlings at 1,236–1,853 trees ha−1 under operational silviculture had the greatest returns at both sites, with mean whole-tree internal rates of return of 8.3%–9.9% assuming stumpage equal to current pulpwood prices. At a 5% discount rate, break-even whole-tree stumpage at the two sites in the optimal treatments was $8.72–$9.92 Mg−1, and break-even yield was 175–177 Mg ha−1 (roughly 18 Mg ha−1 yr−1 productivity), although stumpage and yield floors were higher if only stem biomass was treated as salable. Dedicated short-rotation loblolly biomass plantations in the region are more likely to be financially attractive when site establishment and maintenance costs are minimized.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

A 50-Year Retrospective of the Forest Productivity Cooperative in the Southeastern United States: Regionwide Trials - David R Carter; H Lee Allen; Thomas R Fox; Timothy J Albaugh; Rafael A Rubilar; Otávio C Campoe; Rachel L Cook (Journal of Forestry, 2021)
In 2019, the Forest Productivity Cooperative (FPC) celebrated its 50th anniversary. The mission of the FPC is and has been creating innovative solutions to enhance forest productivity and value through the sustainable management of site resources. This industry-government-university partnership has generated seminal research with sweeping implications for increasing productivity throughout the southeastern United States and Latin America. To commemorate this semicentennial, we highlighted some of the pivotal findings in the southeastern United States from the past 50 years derived from our large, regional experiments: regionwide trials.

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marco A. Yáñez; Eric D. Carbaugh; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Trees, 2020)

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Forest Fertilizer Applications in the Southeastern United States from 1969 to 2016 - Timothy J Albaugh; Thomas R Fox; Rachel L Cook; Jay E Raymond; Rafael A Rubilar; Otávio C Campoe (Forest Science, 2019)

Advances in Silviculture of Intensively Managed Plantations - Rafael A. Rubilar; H. Lee Allen; Thomas R. Fox; Rachel L. Cook; Timothy J. Albaugh; Otávio C. Campoe (Current Forestry Reports, 2018)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Meeting Report: Applied Biopharmaceutics and Quality by Design for Dissolution/Release Specification Setting: Product Quality for Patient Benefit - Arzu Selen; Maria T. Cruañes; Anette Müllertz; Paul A. Dickinson; Jack A. Cook; James E. Polli; Filippos Kesisoglou; John Crison; Kevin C. Johnson; Gordon T. Muirhead; Timothy Schofield; Yi Tsong (The AAPS Journal, 2010)

Aromatic metabolism in the fungi. Growth of Rhodotorula mucilaginosa in p-hydroxybenzoate-limited chemostats and the effect of growth rate on the synthesis of enzymes of the 3-oxoadipate pathway - Timothy J. Huber; John R. Street; Alan T. Bull; Keith A. Cook; Ronald B. Cain (Archives of Microbiology, 1975)